عزل واختيار أفضل العزلات الفطرية من ماء الجفت الطازج لاستخدامها في المعالجة الحيوية - ناصر, أميمة; جنيدي, حسين; موسى, كرم (Latakia University Journal -Basic Sciences Series, 2016)
The aim behind this study was to isolate and characterize fungi from fermented olive mill wastewater to determine the superior one that can resist high organic load and total phenol of fresh Olive Mill Wastewater (OMW).Two different media Czapak Dox Agar (CzA) and Potato Dextrose Agar (PDA) were used for identification of fungi by studying macroscopic and microscopic characteristics. However, Aspergilluss sclerotiorum, Paecilomyces sniveus and Mucor nircinelloides had had been identified . After testing the isolates on fresh olive mill wastewater solid mediums OMWA1 (50%OMW), OMWA2 (75%OMW) and OMWA3 (100%OMW).Whereas P. niveus proves that was the superior one, which can resist high concentration of fresh olive mill wastewater هدف هذه الدراسة هو عزل وتوصيف فطريات من ماء جفت مخمر، وتحديد العزلات الأكثر قدرة على احتمال التراكيز العالية للحمولات العضوية والفينولات الكلية في ماء الجفت الطازج. تم التعرف على ثلاث عزلات تم توصيفها من خلال دراسة الصفات المورفولوجية والبيومترية على وسط الزراعة وسط البطاطا ديكستروز آغار Potato Dextrose Agar (PDA)، ووسط تشابك آغار Czapak Dox Agar (CzA)، وهي عزلة من النوع Aspergillus sclerotiorum وعزلة من النوع Paecilomyces niveus، وعزلة من النوع Mucor nircinelloides. وفي اختبار عزلات الأنواع الثلاث على ثلاثة أوساط اختبارية استخدم فيها ماء الجفت (Olive Mill Wastewater) الطازج بتراكيز OMWA3 (100%OMW) ،OMWA2 (75%OMW) و OMWA1 (50%OMW)، تبين أن العزلة من النوع Paecilomyces niveus هي الأكثر قدرة على احتمال تراكيز عالية من حمولات ماء الجفت الطازج.